(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
This article explores the immersive approach to teaching the English language, emphasizing its pedagogical foundations, practical methods, and benefits for learners. It highlights how immersion creates a natural and effective language acquisition environment by surrounding students with English in real-life contexts. The article outlines strategies such as English-only instruction, task-based learning, role-play, and content integration, while also discussing curriculum design and assessment techniques aligned with immersion. The immersive method promotes language fluency, confidence, and cultural awareness, making it an effective alternative to traditional language teaching methods.